TimeTeller for timing health: The potential of circadian medicine to improve performance, prevent disease and optimize treatment - Dose, Benjamin; Yalçin, Müge; Dries, Sebastian P. M.; Relógio, Angela (Frontiers in Digital Health, 2023)
Circadian medicine, the study of the effects of time on health and disease has seen an uprising in recent years as a means to enhance health and performance, and optimize treatment timing. Our endogenous time generating system -the circadian clock- regulates behavioural, physiological and cellular processes. Disruptions of the clock, via external factors like shift work or jet lag, or internal perturbations such as genetic alterations, are linked to an increased risk of various diseases like obesity, diabetes, cardiovascular diseases and cancer. By aligning an individual's circadian clock with optimal times for performing daily routines, physical and mental performance, and also the effectiveness of certain therapies can be improved. Despite the benefits of circadian medicine, the lack of non-invasive tools for characterizing the clock limits the potential of the field. TimeTeller is a non-invasive molecular/digital tool for the characterization of circadian rhythms and prediction of daily routines, including treatment timing, to unlock the potential of circadian medicine and implementing it in various settings. Given the multiple known and potentially yet unknown dependent health factors of individual circadian rhythms, the utility of this emerging biomarker is best exploited in data driven, personalized medicine use cases, using health information across lifestyle, care, and research settings.